A systematic review of road safety investment appraisal models. Issue 1 (1st January 2021) - Byaruhanga, Chris Bic; Evdorides, Harry
Abstract: It is estimated that 1.35 million people die annually due to road traffic crashes and these crashes cost most countries 3–5% of their gross domestic product (GDP). The economic appraisal of roads considers safety aspects to some extent, but a more explicit approach could add significant value. Therefore, in an attempt to develop a safety-focused model based on the life cycle of measures, this review examines the available models with the view of documenting the current knowledge and its gaps. The review followed the procedures and guidelines developed at the Evidence for Policy and Practice Information and Co-ordinating Centre (EPPI-Centre) together with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The searching and screening process resulted in 12 studies that documented and described the guidelines and methodological framework for SafetyAnalyst, Economic Efficiency Evaluation (E 3 ), the Benefit Cost Analysis (BCA) and the International Road Assessment Programme (iRAP) road safety models. There are no standardized methods for combining life cycle costs of road safety countermeasures during appraisal, and all approaches ignore end of infrastructure life costs. There is neither uniformity nor universally accepted standards to estimate crash or casualty unit costs and the life cycle performance of road safety countermeasures.